Entrepreneurial Clusters as a Model of Spatial Development of Russian Tourism - DZHANDZHUGAZOVA, Elena A.; DUSENKO, Svetlana V.; ROMANOVA, Marianna M.; ORLOVA, Liubov N.; GOLONDAREV, Klim S.; KURBANOV, Salman Abduganievich (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018DO - 10.14505//jemt.v9.4(28).08, 2018)
The relevance of the present study is attributable to the importance of the problem of economic development of Russian territories from the point of view of the retrospective territorial and sector approach, which has currently become widespread. In this respect, the article is aimed at studying and summarizing the cluster approach experience, which allows developing tourism in Russian regions. The authors of the following article focus on the processes occurring in tourist territories in the context of the Federal Target Program (FTP) "Development of Domestic and Incoming Tourism in the Russian Federation". In this regard, the main attention is focused on the best regional practices of cluster development and on the Kuzbass Region as the most original example. The underlying approach to the study of the problem was the allocation of the two key models of cluster formation in tourism: infrastructure and synergistic. The article reveals the elements of cluster policy, identifies the sources of funding for projects, and justifies the role of public-private partnership. The materials of this article are of practical value for the regional government entities, business and academic community.